Listening to the voices of the dead: the 3-11 Tōhoku Disaster speaks - Isomae, Jun'ichi (Michigan Monograph Series in Japanese Studies, 2024)
Listening to the Voices of the Dead is an account of the author's search for disquieted voices of the dead in the wake of the March 11, 2011, Tōhoku Disaster and his attempt to translate those voices for the living. Isomae Jun'ichi considers the disaster a challenge for outside observers to overcome, especially for practitioners of religion and religious studies. He chronicles the care and devotion for the dead shown by ordinary people, people displaced from their homes and loved ones. Drawing upon religious studies, Japanese history, postcolonial studies, and his own experiences during the disaster, Isomae uncovers historical symptoms brought to the surface by the traumas of disaster. Only by listening to the disquiet voices of the dead, translating them, and responding to them can we regain our true selves as well as offer peace to the spirits of the victims. While Listening to the Voices of the Dead focuses on this one event in Japanese history and memory, it captures a broadening critique at the heart of many movements responding to how increasing globalization impacts our sense of place and community